(untitled) - Potash Research Institute of India (Haryana, India, 1989)
This volume is a complain of full papers presented at the symposium on maximum Yeild research held during november 16 to 18, 1988 at Nelhi, India. The papers present experiences of different scientist groups on MYR work conducted in various countries involving different crops, croping systems and soil and climate conditions
Keywords: Crop yields,Crops and soils,Fertilizers,Sản lượng thu hoạch; Congresses,Congresses,Congresses